Daily stair climbing is associated with decreased risk for the metabolic syndrome - Anna C. Whittaker; Frank F. Eves; Douglas Carroll; Tessa J. Roseboom; Annie T. Ginty; Rebecca C. Painter; Susanne R. de Rooij (BMC, 2021)
Abstract Background Stair climbing can be a vigorous lifestyle physical activity, and is associated with healthier lipoprotein profiles, lower body weight and blood pressure, as well as higher aerobic fitness. The present analysis of data from a cohort of late middle-aged men and women examined the association between daily stair climbing and the metabolic syndrome. Methods Data from 782 (423 women) participants (mean (SD) age 58.3 (0.95) years in the Dutch Famine Birth Cohort Study (2002-2004) were used to examine the cross-sectional association between self-reported daily stair climbing and the metabolic syndrome. Stair climbing was assessed by the question 'Do you climb stairs daily?' and the metabolic syndrome was defined using the established five components relating to lipid fractions, blood glucose levels, blood pressure and abdominal obesity. Results Not climbing stairs daily was associated with an increased incidence of the metabolic syndrome (OR = 1.90, 95% CI = 1.23, 2.92, p = 0.004) and a greater number of its components (F1,780 = 8.48, p = 0.004): these associations were still evident after adjusting for a variety of potential confounders. Conclusions The most likely explanation for the current findings is that daily stair climbing may be protective against the metabolic syndrome. This result reinforces public health recommendations for increased stair climbing with evidence from physiological outcomes.